Study of hematological parameters in anemia in pregnancy - Sharan, Anita; Shah, Sagar (Tropical Journal of Pathology and Microbiology, 2019)
Background: To evaluate the major hematological parameters and morphological typing in anemic pregnant females and correlation of the above findings with the trimester and gravid status of the patient. Material and Methods: This study was conducted on 250 pregnant women attending antenatal OPD having hemoglobin level less than 11 gm/dl in 1st and 3rd trimesters and less than 10.5 gm/dl in the 2nd trimester. Age, gravida, trimester, educational status of each pregnant subject was noted as well as grading and morphological typing of anemia was done. Results: Maximum number of cases were found in age group of 21-30 years i.e. 79.2% (198 cases out of 250 cases). Maximum number of cases of anemic pregnant subjects were primigravidae i.e. 42%. Highest percentage of anemia was in third trimester i.e. 52.4% (131 out of 250 cases). Among all morphological types microcytic hypochromic anemia was most predominant i.e. 89.2%. Moderate anemia was the predominant grade of anemia i.e. 67.6% (169 out of 250). On correlating age group with grade of anemia, moderate anemia was found to be predominant among all age groups. Out of 169 cases of moderate anemia, 74 cases (43.8%) were in 21-25 age group. Conclusion: All the four factors i.e. age, gravida, trimester and educational status were correlated with grade and morphological type of anemia. Microcytic hypochromic anemia was the predominant morphological type of anemia in all age ranges, all gravidae and all trimesters. There was statistically significant association between age and morphological type of anemia.